Prevalence and associated factors of choroidal cavern in patients with type 2 diabetes mellitus - Vidal Oliver, Lourdes; Spissinger, Sabrina; Herzig de Almeida, Elisa; Garzone, Davide; Chronopoulos, Argyrios; Finger, Robert P. (Retina, 2025)
Purpose: - To study the prevalence of choroidal caverns (CCs) in patients with Type 2 diabetes (T2DM) and their association with demographic and clinical data. - Methods: - Patients with T2DM and nondiabetic control subjects were included in a cross-sectional, monocenter study. The main outcome measure was the presence of CCs. Exploratory variables included age, sex, diabetic retinopathy status, duration of T2DM, visual acuity, arterial hypertension, hyperlipidemia, HbA1c, choroidal thickness and choroidal vascularity index. Group differences between eyes with and without CCs and associations with demographic and clinical variables were assessed. - Results: - After including a total of 205 eyes of 116 patients, the prevalence of CCs was 25% in the control, 28% in the T2DM without diabetic retinopathy, and 9.5% in the diabetic retinopathy groups. The locations of the caverns were choriocapillaris (N = 2, 4.2%), Sattler layer (N = 29, 60.4%), and Haller layer (N = 17, 35.4%). In total, 34.3% of patients had caverns in both eyes. No significant differences were found in systemic conditions (including arterial hypertension, hyperlipidemia, HbA1c, or T2DM disease duration). Choroidal vascularity index was the only parameter independently associated with the presence of CCs (OR 1.37). - Conclusion: - The authors found CCs in almost a quarter of patients with and without T2DM. Choroidal caverns were mainly located in the Sattler layer. Choroidal vascularity index was independently associated with the presence of CCs. These findings suggest that the presence of CCs may be a sign of a higher metabolic activity within the choroidal microenvironment, irrespective of T2DM status.
Gesehen am 01.07.2025